The challenges of health professionals in meeting the needs of vulnerable patients undergoing chemotherapy: a focus group study. Issue 19 (20th March 2014) - Witham, Gary; Haigh, Carol; Foy, Sharon
<x xml:space="preserve">Abstract</x> Aims and objectives To explore health professionals' perceptions of the needs of patients undergoing chemotherapy treatment for cancer. Background Patients with vulnerabilities face additional challenges. People with learning difficulties are often protected from even basic cancer information; patients with severe mental illness are open to structural discrimination with limited access to diagnostic and treatment services. There is also a much poorer survival rate after a cancer diagnosis for patients living with dementia. Design A qualitative design was used. Methods A focus group design was undertaken for this project using a narrative analytical approach revealing how narrative tales are presented and performed. Eighteen healthcare workers were recruited from a regional oncology centre in North West England. Two focus groups were conducted with nine participants in each. The data were collected from late 2011–2012. Results Participants were primarily focused on getting patients through treatment. The identification of vulnerability was an 'extra' complication and one that in practice was difficult to define/categorise. The participants appreciated the wider inclusion of family and friends to support vulnerable patients although they felt formalised health care was not particularly facilitative of this process. There were difficulties in achieving support for complex patient needs in the presence of a target driven culture. Conclusions Healthcare professionals need wider managerial and cultural support in meeting the needs of vulnerable patients. There appeared to be a tendency by healthcare professionals to minimise the inherent coping abilities of vulnerable patients. Relevance to clinical practice There is a clear need to support health professionals in providing appropriate resources in order to address the complex needs of vulnerable patients. This requires a cultural shift away from targets and an investment into greater resources for effective multidisciplinary working.